PENDIDIKAN ISLAM DALAM PERSPEKTIF EPISTEMOLOGI BURHANIY - Muhamad Asvin Abdur Rohman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2016)
Soebardi in The Place of Islam states that: (a) institutions boarding schools are the institutions most decisive Islamic character of Islamic kingdoms and the most important role for the spread of Islam to the outposts; (B) of the institutions of boarding that origins a number of manuscripts concerning the teaching of Islam in Southeast Asia, (c) and to be able to truly understand the history of Islamization in the region, we should begin to study these boarding institutions, because tutions is the primary agency arrows spread of Islam in the region. Pesantren education today can be classified into three types. First, the boarding school education and teaching how to use the method sorogan or dam, which is a teaching Kyai of santri based on the classic books written in Arabic, by scholars' medieval translation system. Generall, boarding school is "stiril" of general science. People usually call it by name salaf pesantren. Second, in addition to maintaining the boarding school and teaching systems, as mentioned above, also includes public education. Third, schools as the education system and teaching models integrates into schools with one the soul, and the value of other attributes, and teaching wear classical system coupled with strict discipline with full dormitories or students are required to reside in the hostel. The specific objective education pesantren is to prepare the students to become people 'alim in the science of religion taught by clerics concerned and put it into practice in the community. While the general purpose schools is to guide students into human personality capable of Islam with religious knowledge became muballig in the surrounding communities through science and charity.